2001
DOI: 10.1021/ma0012999
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Ultrathin Polystyrene Films Using a Two-Step Deposition/Polymerization Process

Abstract: Thin polystyrene films were formed on polycrystalline platinum by styrene deposition followed by UV-initiated polymerization under cryogenic, ultrahigh-vacuum conditions. Temperature-programmed desorption (TPD) experiments showed that styrene chemisorbs weakly on the Pt surface. In the temperature region of 115−145 K, the adsorbed styrene films undergo a crystallization process that can be described by the Avrami equation. The polymerization rate increased with incident UV intensity, as expected, but was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 29 publications
(31 reference statements)
2
15
0
Order By: Relevance
“…The experimental results [33][34][35][36] were fitted using the Johnson-Mehl-Avrami equation (JMA), given by…”
Section: Resultsmentioning
confidence: 99%
“…The experimental results [33][34][35][36] were fitted using the Johnson-Mehl-Avrami equation (JMA), given by…”
Section: Resultsmentioning
confidence: 99%
“…Recently, our group reported that the vapor deposition polymerization (VDP) technique allows a simple route for the synthesis of inorganic-polymer and inorganic-carbon core-shell nanostructures by consecutive polymerization of vaporized monomer under vacuum onto the desired surface. 8 So far, VDP has been mainly performed to fabricate various thin films and core-shell nanostructures, 9 whereas considerably less attention has been paid to the application of VDP in colloidal templating. The VDP process makes it possible for monomer vapor to be polymerized even inside very small void spaces between colloidal particles without disrupting the characteristic of the colloidal template structure.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6] Many advanced applications of ultrathin polymer films can be envisioned, such as all polymeric semiconducting devices and direct-write lithography [5,6]. Currently, the most common method to prepare thin polymer films is by wet techniques, such as electrochemical deposition, spin coating.…”
Section: Introductionmentioning
confidence: 99%
“…The characterizations of the films were carried out using ex-situ Fourier transformationinfrared-reflection absorption spectroscopy (FT-IR-RAS), X-ray photoelectron spectroscopy (XPS), optical microscopy and atomic force microscopy (AFM). Figure 1 shows FT-IR-RAS spectra of 6-diallylamino- [1,3,5]triazine-2,4-dithiol (DA) thin films of 50 nm UV irritated at various times. Table 1 summarizes the main absorption bands found in the spectra and their associated vibration modes.…”
Section: Introductionmentioning
confidence: 99%